1980
DOI: 10.1161/01.cir.62.3.564
|View full text |Cite
|
Sign up to set email alerts
|

Serial echocardiographic evaluation of left ventricular function in valvular disease, including reproducibility guidelines for serial studies.

Abstract: SUMMARY Longitudinal echocardiographic studies of left ventricular (LV) function in valvular disease were evaluated in 24 medically treated patients followed for 6 months to 3 years (mean 16.3 months) and in 22 surgically treated patients before and at least 1 year after operation (mean 14 months). In initial reproducibility studies of enlarged hearts (mean end-diastolic dimension [EDDI 6.6

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

1984
1984
2004
2004

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(11 citation statements)
references
References 34 publications
(5 reference statements)
1
10
0
Order By: Relevance
“…[17][18][19] LV filling was assessed from conventional evaluation of the early maximum (E) and atrial (A) LV filling inflow velocities and their ratio (E/A). 20…”
Section: Doppler Echocardiographymentioning
confidence: 99%
“…[17][18][19] LV filling was assessed from conventional evaluation of the early maximum (E) and atrial (A) LV filling inflow velocities and their ratio (E/A). 20…”
Section: Doppler Echocardiographymentioning
confidence: 99%
“…The use of serial echocardiographic measurements of left ventricular dimensions and function has been ham-pered by problems of measurement reproducibility [1][2][3] . Variability and bias in quantitative echocardiography are introduced both during image acquisition and by measuring cardiac dimensions and derived function.…”
Section: Introductionmentioning
confidence: 99%
“…Variability and bias in quantitative echocardiography are introduced both during image acquisition and by measuring cardiac dimensions and derived function. Despite little difference between means, the 95% confidence interval for a single replicate measurement is often wide [2][3][4][5][6] . Serial studies introduce temporal variation of the reader and regression to the mean as additional sources of variability and bias [1] .…”
Section: Introductionmentioning
confidence: 99%
“…Echophonocardiographic measurements were, therefore, repeated at intervals over several months. Although reproducibility studies were not performed, others "' 14 19 have shown a small standard deviation for systolic time intervals (for example 5 ms 217 for left ventricular ejection time; 4 ms for pre-ejection period) and for velocity of circumferential fibre shortening (0.05 circumferences per s) when repeated at intervals over weeks in the same subjects. A preliminary study of four normal subjects on four separate occasions using the above protocol showed similar day to day variability in these indices.…”
mentioning
confidence: 97%